Analysis of eating behaviors and eating habits, body mass index and waist-to-hip ratio in association with spirometry results of young adults - Dzięciołowska-Baran, Edyta; Mularczyk, Maciej; Gawlikowska-Sroka, Aleksandra; Michnik, Kinga; Rębacz-Maron, Ewa (Anthropological Review, 2017)
Behavior and eating habits stands as an important factor in terms of maintaining a good health condition in every age group. This involves optimal digestion, maintaining proper metabolism of the entire organism and thus maintaining proper body weight. It is especially important for students, as the increased mental activity results in increased energy expenditure. The state of body weight can affect the respiratory efficiency measured in spirometry. The aim of the study was to assessthe relation between behavior and eating habits, body mass index (BMI), waist-to-hip ratio (WHR) and results from spirometry tests among young adults. The study sample included 185 students from the University of Szczecin (mean age 21.2±1.3). Using a questionnaire prepared for the study, information on the eating plan of students for three consecutive days was collected. Dietary analysis was concerned with: eating in stressful situations, dieting, regularity of main meals, eating between main meals. Afterwards spirometry examination was performed along with a detailed measurement of body weight and height, waist and hip circumferences in order to calculate BMI and WHR index of each respondent. The data obtained was processed statistically. Significant correlations between FVC and “dieting” (Spearman’s rs=0.3) were recorded in the group of women. However, the association of other behavior and eating habits with spirometry parameters did reveal null results in both males and females. Correct behaviors and eating habits at a young age affect spirometry parameters to a negligible extent. The absence of direct health related effects of bad consumption habits at a young age makes it all the more important to raise the awareness of students, that their current decisions will have an apparent effect in the future, maybe only after a few years.